2011
DOI: 10.1158/1541-7786.mcr-10-0598
|View full text |Cite
|
Sign up to set email alerts
|

Control of VEGF Expression in Triple-Negative Breast Carcinoma Cells by Suppression of SAF-1 Transcription Factor Activity

Abstract: Angiogenesis plays a significant role in cancer by providing increased blood supply to the affected tissues and thus bringing in growth factors, cytokines, and various nutrients for tumor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 51 publications
0
37
0
Order By: Relevance
“…Ray et al (31) recently showed that MAZ can induce the transcriptional activation of VEGF in breast cancer cells. In line with these results, we observed that MAZ knockdown significantly reduced VEGF mRNA expression in hCMEC/D3 cells ( Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Ray et al (31) recently showed that MAZ can induce the transcriptional activation of VEGF in breast cancer cells. In line with these results, we observed that MAZ knockdown significantly reduced VEGF mRNA expression in hCMEC/D3 cells ( Fig .…”
Section: Resultsmentioning
confidence: 99%
“…MAZ is a zinc finger transcription factor that binds to GpCrich cis-elements in the promoter regions of numerous mammalian genes and is also able to recruit different proteins, such as methylases and acetylases, to the transcriptional complex, thereby acting as an initiator or terminator of transcription. 31 The transcription factor has been implicated in VEGF-induced angiogenesis 16,32,33 ; this effect being negatively controlled by microRNA-125b, of which MAZ is an inhibitory target. 16 Of note, we found that the expression of microRNA-125b in SV-APCs is inversely correlated with their ability to induce reparative vascularization in the mouse LI model.…”
Section: Discussionmentioning
confidence: 99%
“…56 Increases in serum SAA correlate with carcinogenesis and neoplastic progression; SAA is proposed as a biomarker for a variety of human cancers, 56 including lung, 57 colorectal 58 , renal, 59 ovarian, 60 and breast cancer. 61 The SAA gene is induced by IL-6 when stimulated with proinflammatory cytokines. 62 SAA is also regulated by an activating factor (SAF-1) that is linked to VEGF expression and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%